Synthesis of 2-Hydroxyethyl Esters from Castor Oil as Lubrication Bio-Additive Candidates for Low-Sulfur Fossil Diesel - Yulfi Zetra; Didik Prasetyoko; Novesar Jamarun; Arizal Firmansyah; Rafwan Year Perry Burhan (Indonesian Journal of Chemistry, 2022)
The present work aims to study the synthesis of 2-hydroxyethyl esters from castor oil and its lubrication properties, promising as a lubrication bio-additive in low sulfur diesel fuel. This compound has been successfully synthesized from castor oil and ethylene glycol. The oil to ethylene glycol molar ratio was adjusted to 1:10, and the catalyst loading was used at 9% mole oil. Then, the mixture was refluxed for 5 h. The product components were characterized using GC-MS. The standard ASTM method was used to study the kinematic viscosity and lubrication. The product was dominated by 2-hydroxyethyl esters (94.16%), di-ester (1.12%), and cyclic ester (1.92%). The analysis of friction coefficient and wear scar diameter (WSD) using High-Frequency Reciprocating Rig (HFRR) shows the coefficient of friction and WSD of the product better than reference diesel fuel. From the results of this study, the 2-hydroxyethyl ester of castor oil, especially 2-hydroxyethyl ricinoleate, is the main responsible for the lubricating properties. Thus, 2-hydroxyethyl esters of castor oil can be proposed as an alternative bio-additive to improve the lubrication of low-sulfur fossil diesel fuels.